AN ANALYSIS OF TENSES USAGE IN ANIMATED MOVIE â€œUPâ€: The relevance with 2013 curriculum for teaching EFL at junior high school in Indonesia - Nuzulul Isna (Englisia: Journal of Language, Education, and Humanities, 2018)
Movies have been seen as an encouraging media in learning English, tuning out the formal fear of English. They have helped increase students’ confidence and initiative to ask and answer the questions, and improve their listening skill and attention span in English drastically (O'Donnell, 1990). This article is intended to seek the applicability of the English sentences used in the movie Up and their uses for EFL learning in Indonesia. The 2013 curriculum was used as the standard guideline to determine the sentences’ appropriateness. A qualitative research by imposing content analysis method was employed to conduct the data analysis in this article. The findings classified the specific numbers of sentences generated in this research into ten (10) categories of English tenses. Another finding also indicated the applicability of those sentences for teaching EFL/ESL in junior high schools. Remarkably, these findings were substantial for appending the teachers’ resources in teaching English tenses.